2012
DOI: 10.1111/j.1360-0443.2012.04038.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting treatment for neonatal abstinence syndrome in infants born to women maintained on opioid agonist medication

Abstract: Aim To identify factors that predict the expression of neonatal abstinence syndrome (NAS) in infants exposed to methadone or buprenorphine in utero. Design and Setting Multi-site randomized clinical trial in which infants were observed for a minimum of 10 days following birth, and assessed for NAS symptoms by trained raters. Participants n = 131 infants born to opioid dependent mothers, 129 of which were available for NAS assessment. Measurements Generalized linear modeling was performed using maternal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 35 publications
0
76
1
1
Order By: Relevance
“…Some reports suggest that the use of tobacco and coprescription of selective serotonin reuptake inhibitors (SSRIs) may also increase the likelihood of developing NAS. [10][11][12] Using a large retrospective cohort of pregnant women, our objectives were to identify neonatal complications associated with antenatal OPR exposures and to determine if antenatal cumulative prescription opioid exposure, opioid type, number of cigarettes smoked daily, and SSRI use were associated with a higher likelihood of developing NAS.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports suggest that the use of tobacco and coprescription of selective serotonin reuptake inhibitors (SSRIs) may also increase the likelihood of developing NAS. [10][11][12] Using a large retrospective cohort of pregnant women, our objectives were to identify neonatal complications associated with antenatal OPR exposures and to determine if antenatal cumulative prescription opioid exposure, opioid type, number of cigarettes smoked daily, and SSRI use were associated with a higher likelihood of developing NAS.…”
Section: What This Study Addsmentioning
confidence: 99%
“…8,9 Furthermore, our findings provide important information that builds on previous studies of OPR use in pregnancy 3,35,36 and several publications describing tobacco and SSRI use in the context of opioid maintenance. [10][11][12] Both tobacco and SSRIs have been described in the literature as having individual withdrawal syndromes and unique toxidromes. 5 Nevertheless, these exposures could also be associated with a constellation of other risk factors that may be difficult to measure directly (eg, substance abuse) and account for in our analyses.…”
Section: Figurementioning
confidence: 99%
“…In a secondary analysis of the MOTHER study, Kaltenbach and colleagues found that greater nicotine use at delivery (defined by number of cigarettes smoked in the twenty-four hours prior to birth) was associated with higher rates of treatment for NAS as well as the total dose of medication required. 61 However, maternal nicotine use did not correlate with higher peak NAS scores or duration of treatment. The same study also examined the relationship between SSRIs and the development of NAS.…”
Section: Predictive Factorsmentioning
confidence: 86%
“…NAS requiring pharmacotherapy occurs in 22–67% (Kocherlakota, 2014) among buprenorphine-exposed infants. Substances that may potentiate NAS severity in methadone-exposed infants include polysubstance exposures (Jansson et al, 2012), heavy cigarette smoking (Choo et al, 2004) and psychiatric medication, particularly SRIs (Kaltenbach et al, 2012). It is unknown whether these substances similarly predispose the infant to more severe NAS in buprenorphine-exposed pregnancies, or if other aspects of exposure, such as maternal buprenorphine dose, potentiates NAS in exposed infants.…”
Section: Introductionmentioning
confidence: 99%